Developing Multicultural Values–Based Teaching Materials for Developmental Psychology in Islamic Education at the Islamic University of Depok - Miftahul Huda (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study is motivated by the fact that students of Universitas Islam Depok are distributed across 16 provinces in Indonesia. This condition indicates that students come from diverse backgrounds in terms of culture, religion, ethnicity, customs, traditions, and language. However, the Developmental Psychology course in Islamic Education has not yet been supported by teaching materials that incorporate multicultural values in accordance with this diversity. This study aims to develop multicultural values–based teaching materials for Developmental Psychology in Islamic Education at Universitas Islam Depok and to examine the validity and practicality of the developed materials, the research method employed is research and development (R&D) using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, and questionnaires. The sources of data in this study were students and lecturers of Developmental Psychology in Islamic Education. The object of the study was multicultural values–based teaching materials for Developmental Psychology in Islamic Education, the results of this study show that the development of teaching materials for Developmental Psychology in Islamic Education followed the ADDIE model and produced a final product in the form of a textbook entitled “Developmental Psychology in Islamic Education Based on Multicultural Values.” The textbook consists of a cover, preface, table of contents, 14 chapters of materials integrated with multicultural values, summaries in each chapter, discussion materials, chapter-specific references, practice exercises, a comprehensive bibliography, glossary, index, and book synopsis. The validity test results of the developed teaching materials yielded an average percentage score of 95.45%, categorized as very valid, while the practicality test resulted in an average percentage score of 87.5%, categorized as very practical. Therefore, these teaching materials are considered highly valid and highly practical, making them suitable for use in the Developmental Psychology course in Islamic Education.